(untitled) (Palestine Issues on Indonesian Society, 2025)
This paper examines the impact of the Gaza crisis on social movements and political expressions in Indonesia, focusing on how the ongoing conflict shapes local activism, public opinion, and political engagement. Drawing on case studies of demonstrations, social media campaigns, and public protests, the study investigates how the humanitarian situation in Gaza has fueled solidarity movements, particularly within Indonesian Muslim communities. It explores the ways in which the Gaza crisis has become a rallying point for grassroots activism, as well as how it has been used by political actors to mobilize support for Palestinian rights. The paper also considers the influence of international media coverage on the local discourse surrounding Gaza, and how the crisis has influenced debates on Indonesia’s foreign policy towards the Middle East. By assessing the role of the Gaza conflict in shaping Indonesian political expression, this study highlights the intersection between international events and domestic political dynamics, especially in terms of solidarity, religion, and social justice movements.